The Risk Factors of Self-Management Behavior among Chinese Stroke Patients - Huang Shuqi; Li Siqin; Wu Xiaoyan; Yang Rong; Zhao Lihong (International Journal of Clinical Practice)
Background. Stroke is associated with a high number of disability-adjusted life years globally, so long-term care is necessary and important for those survivors, so self-management is becoming a more significant concept in stroke rehabilitation. Methods. Ischemic stroke patients (n = 354) were enrolled from the outpatient department of Neurology in West China Hospital from September 2018 to December 2019. The general demographic and disease-related data of stroke patients were collected. The stroke self-efficacy questionnaire (SSEQ), the brief cognition questionnaire (BIPQ), and the stroke self-management scale (SSMS) were used to collect data on self-efficacy, disease cognition, and self-management behavior separately. The chi-square test, Fisher exact test, independent sample t-test, and Mann–Whitney U test were used for comparison among groups. The logistic regression analysis was used to explore the independent risk factors of the different levels of self-management behavior in stroke patients. Results. The score of self-management among Chinese stroke patients was 151.07 ± 18.53. Multivariate analysis showed that the way of paying medical expenses (OR = 3.215, 95% CI (1.130, 7.769)), self-management efficacy (OR = 2.467, 95% CI (1.534, 3.968)), health education before discharge (OR = 2.354, 95% CI (1.457, 3.802)), age (elder) (OR = 2.060, 95% CI (1.265, 3.355)), educational level (OR = 1.869, 95% CI (1.169, 2.988)), and mRS score (OR = 1.850, 95% CI (1.129, 3.031)) were statistically significant (P < 0.05). Conclusions. The self-management behavior of Chinese stroke patients was at the middle level. Patients with medical insurance, high self-efficiency of management, and better limb function may have better self-management behavior. Besides, patients with a high educational level who accept health education before discharge may also have better self-management behavior. For patients, it is important to know this disease in the right way and set up the faith to take care of themselves independently gradually. For medical staff, it is necessary and important to give all patients health education about self-management before discharge. It is urgent to call for attention to this disease, and the government and all of society should give more support to stroke patients.